The oldest Diptera (Insecta) from the Upper Buntsandstein (early Middle Triassic) of Europe - Lukashevich , Elena D. (Zootaxa, 2021)
The fossil record of Triassic Diptera is still poor, with the oldest dipteran assemblage described from the Upper Buntsandstein of the ‘Grès à Voltzia’ Formation (early Anisian, France). From the stratigraphically closest insect fauna of the Röt Formation of Lower Franconia, Germany, the first Diptera, Bashkonia franconica gen. et sp. nov. is described based on an isolated wing. The new genus is assigned to the family Nadipteridae, bridging the gap between two other genera included.